Literature Review: The Use of Long-Lived Isotopes in Satellite Electrical Power Systems - Nirwana; Wahyuni; Nurmila, St; Irfanita, Resky (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
The use of long-lived isotopes as an energy source in satellite electrical power systems has become a significant focus in modern space technology. One such isotope, Plutonium-238, generates energy through radioactive decay over an extended period, enabling satellites to operate in extreme environments with minimal sunlight. This study aims to gather and analyze literature on the application of long-lived isotopes to enhance the sustainability and reliability of satellite power systems. The method employed is a literature review, which involves examining articles from various academic databases. The data sources consist of six scientific articles and one book relevant to the topic. Findings indicate that the use of long-lived radioactive isotopes, such as Plutonium-238 and Americium-241, has proven effective in sustaining satellite electrical power systems, particularly through Radioisotope Thermoelectric Generator (RTG) technology. These isotopes generate heat through radioactive decay, which is subsequently converted into electrical energy, allowing satellites to operate in extreme conditions and without relying on solar exposure.